Initial Discharge Capacity of Manganese Cobaltite as Anode Material for Lithium Ion Batteries - Mehrdad Dorri; Cyrus Zamani; Alireza Babaei (Journal of Ultrafine Grained and Nanostructured Materials, 2018)
Nanostructured manganese cobalt oxide spinel (MnCo2O4) are prepared by co-precipitation method and calcined at 650 and 750°C. Morphological studies show that by increasing the calcination temperature from 650 to 750°C, morphology of the particles changes from quasi-plate to polyhedral. The MnCo2O4 calcined at 650°C could deliver an initial discharge capacity of 1438 mAh g-1 under current density of 45 mA g-1. The effects of calcination temperature on the initial discharge capacity of the electrode have also been investigated, The MnCo2O4 calcined at 650°C shows the higher initial discharge capacity due to the higher surface area (due to smaller particles) and weaker crystallinity. The influences of electrode porosities also have been studied, which suggest the electrochemical performance is determined by both the particle-to-particle contact and wettability of the electrode. An increase of the internal resistance of the electrode is observed with increasing electrode thickness (active material loading), which is the main factor responsible for the significant capacity loss for thicker electrode.